Sandwich Structures with Prismatic and Foam Cores: A Review. Issue 1 (23rd October 2018) - Xiong, Jian; Du, Yuntong; Mousanezhad, Davood; Eydani Asl, Mohamad; Norato, Julián; Vaziri, Ashkan
Abstract : This article provides a comprehensive review of recent research efforts on the development and characterization of sandwich structures with corrugated, honeycomb, and foam cores. The topics discussed in this review article include aspects of core‐face bonding and reinforcement, enhancement of core mechanical properties and panel performance (including the role of structural hierarchy), and multifunctional advantages offered by different core constructions. In addition, the review discusses potential applications, including in morphing wing design, impact resistance, and ultralightweight applications. Future research directions are discussed. Abstract : This article provides a comprehensive review of the current state of the art of sandwich structures including corrugated sandwich structures, honeycomb sandwich structures, and foam sandwich structures. The topics mainly consist of core‐face bonding and reinforcement, enhancement of core mechanical properties and panel performance, and tailoring properties for each core type.